Knowledge and Confidence of a Convenience Sample of Australasian Emergency Doctors in Managing Dental Emergencies: Results of a Survey - Hossein Samaei; Tracey Joy Weiland; Stuart Dilley; George Alexander Jelinek (Emergency Medicine International)
Background. We aimed to determine Australasian Specialist Emergency Physicians’ and Emergency Physicians in Training (Trainees’) level of knowledge of common dental emergencies. We also explored confidence in managing dental emergencies; predictors of confidence and knowledge; and preferences for further dental education. Methods. A questionnaire was distributed electronically (September 2011) and directly (November 2011) to Fellows and Trainees of the Australasian College for Emergency Medicine. It explored demographics, confidence, knowledge of dental emergencies, and educational preferences. Results. Response rate was 13.6% (464/3405) and college members were proportionally represented by region. Fewer than half (186/446; 42%) had received dental training. Sixty-two percent (244/391, 95% CI 57.5–67.1) passed (>50%) a knowledge test. More than 60% incorrectly answered questions on dental fracture, periodontal abscess, tooth eruption dates, and ulcerative gingivitis. Forty percent (166/416) incorrectly answered a question about Ludwig’s Angina. Eighty-three percent (360/433) were confident in the pharmacological management of toothache but only 26% (112/434) confident in recognizing periodontal disease. Knowledge was correlated with confidence (r=0.488). Interactive workshops were preferred by most (386/415, 93%). Conclusions. The knowledge and confidence of Australasian Emergency Physicians and Trainees in managing dental emergencies are varied, yet correlated. Interactive training sessions in dental emergencies are warranted.